Effects of the alpha-mannosidase inhibitors, 1,4-dideoxy-1,4-imino-D-mannitol and swainsonine, on glycoprotein catabolism in cultured macrophages. - Daniel, P; Newburg, D; O'Neil, N; Smith, P; Fleet, G (1989)
Thioglycollate-stimulated murine peritoneal macrophages were cultured for eight days in the presence of swainsonine, or 1,4-dideoxy-1,4-imino-D-mannitol (DIM), or both of these competitive alpha-mannosidase inhibitors together. Analysis of accumulated high-mannose oligosaccharides by reversed phase HPLC after perbenzoylation revealed that DIM- and DIM-plus swainsonine-treated macrophages contained larger amounts of Man7GlcNAc, Man8GlcNAc and Man9GlcNAc, while swainsonine-treated macrophages contained relatively more Man3GlcNAc and Man5GlcNAc. These results are consistent with the known inhibitory effects of DIM and swainsonine on Golgi mannosidases I and II, respectively, and on lysosomal alpha-mannosidase. Depletion of stored oligosaccharides to control values was complete within seven days of terminating swainsonine treatment.